Identifikasi Teks dari Citra Menggunakan Optical Character Recognition - Fadjeri, Akhmad (Jurnal Ilmiah SINUS, 2024)
Writing is a human activity to gather information. Now the media of writing is not only on paper but in digital writing on computers.As a person who works as a writer,often come across documents in which there is quite a lot of text.To input text into the computerof course it take a longe time if typed manually one by one. Incomputer science, there isa field of science is call image processing, in this case it can be used as a method to make it easier in these conditions.Generally to input text into the computer the autor handles it manually with the keyboard, but with image processing we can process an image into a text that can be directly processed by the computer. From these problem, a program was created that can convert an image into text using the pythin programming language.To convert image into text using the tesseract module.Tested using 10 sample image taken form the internet and camera photos, the results obtained that programming using image processing with the python programming language is able to convert an image inti text with an accuracy rate of 76 %.